Durability Determination of the Bearing Structure of an Open Freight Wagon Body Made of Round Pipes during its Transportation on the Railway Ferry - Fomin, Oleksij; Gerlici, Juraj; Lovska, Alyona; Kravchenko, Kateryna; Prokopenko, Pavlo; Fomina, Anna; Hauser, Vladimir (Communications - Scientific letters of the University of Zilina, 2019)
In order to reduce the cost of designing and manufacturing of the new-generation open wagons, it is proposed to construct their carrying systems from round pipes. In order to exploit the proposed designs of wagons in international rail-water communication, it is assumed that they will be equipped with assemblies for fastening of chain binders. The maximal values of accelerations, as components of dynamic load acting on open wagons, made from round pipes during their transportation on a railway ferry, are determined. It is established that when moving the body in the vertical direction for a wagon located on the upper deck, the maximum acceleration value is 0.84g, with angular displacement relative to the transverse axis for the extreme from the anchor point of the wagon body - is 0.1 g, with angular displacement around the longitudinal axis for the extreme from the bulwark of the body of the wagon - is 0.24g. The conducted researches will enable increased efficiency of operation of open wagons through international transport corridors.